Chromatin looping as a target for altering erythroid gene expression - Krivega, Ivan (Ann N Y Acad Sci, 2016)
The β-hemoglobinopathies are the most common monogenic disorders in humans, with symptoms arising after birth when the fetal γ-globin genes are silenced and the adult β-globin gene is activated. There is a growing appreciation that genome organization and the folding of chromosomes are key determinants of gene transcription. Underlying this function is the activity of transcriptional enhancers that increase the transcription of target genes over long linear distances. To accomplish this, enhancers engage in close physical contact with target promoters through chromosome folding or looping that is orchestrated by protein complexes that bind to both sites and stabilize their interaction. We find that enhancer activity can be redirected with concommitant changes in gene transcription. Both targeting the β-globin locus control region to the γ-globin gene in adult erythroid cells by tethering and epigenetic unmasking of a silenced γ-globin gene lead to increased frequency of LCR/γ-globin contacts and reduced LCR/β-globin contacts. The outcome of these manipulations is robust, pancellular γ-globin transcription activation with a concomitant reduction in β-globin transcription. These examples show that chromosome looping may be considered a therapeutic target for gene activation in β-thalassemia and sickle cell disease.